The Implementation of the Think Pair Share (TPS) Learning Model to Increase Student Activeness in Pancasila Education Subjects: Penerapan Model Pembelajaran Think Pair Share (Tps) Untuk Meningkatkan Keaktifan Siswa Pada Mata Pelajaran Pendidikan Pancasila - Mutakin, Deden; boli, syaifullah (Citizenship Education, Faculty of Education, Jambi University, 2025)
In learning Pancasila Education in class X F Muallimin Muhammadiyah Yogyakarta Madrasah has not seen the activeness of participants such as responding to questions, helping each other and cooperating and expressing opinions. It takes a Think Pair Share (TPS) learning model that can increase activeness (collaborative activity) in the learning process. The purpose of this study was to determine student activeness after applying the Think Pair Share (TPS) learning model. This research is a class action research (PTK) with the application of Think Pair Share (TPS) learning model. This research was carried out in two cycles of action with four stages that are commonly passed, namely (1) planning, (2) implementation, (3) observation, and (4) reflection. The subjects of this study were students of class X F who were low in creativity. The research was conducted on November 4 - December 8, 2024. The results of this study on student activeness in learning Pancasila Education in class X F can be improved using the Think Pair Share (TPS) learning model. Pancasila Education learning becomes more interesting for students and can influence students to be actively involved in learning.